Selected, Adopted and Implemented Social-Emotional Learning Program: the Kindness Curriculum for Kids - Hakan Uşakli (Educational Challenges)
The aim of this manuscript is to introduce the program of social-emotional learning. Developed by the Centre for Healthy Minds (CHM) this program is called the Kindness Curriculum (CHM, 2017). Founded by the world renowned neuroscientist Dr. Richard J. Davidson, the Centre for Healthy Minds offers a kinder, wiser, more compassionate world.